Experimental Mapping of the Canine KCNJ2 and KCNJ12 Gene Structures and Functional Analysis of the Canine KIR2.2 ion Channel - Houtman, Marien J.; Takanari, Hiroki; Kok, Bart G.; van Eck, Margot; Montagne, Denise R.; Vos, Marc A.; de Boer, Teun P.; van der Heyden, Marcel A. (Frontiers in Physiology, 2012)
For many model organisms traditionally in use for cardiac electrophysiological studies, characterization of ion channel genes is lacking. We focused here on two genes encoding the inward rectifier current, KCNJ2 and KCNJ12, in the dog heart. A combination of RT-PCR, 5’-RACE and 3’-RACE demonstrated the status of KCNJ2 as a two-exon gene. The complete open reading frame was located on the second exon. One transcription initiation site was mapped. Four differential transcription termination sites were found downstream of two consensus poly-adenylation signals. The canine KCNJ12 gene was found to consist of three exons, with its open reading frame located on the third exon. One transcription initiation and one termination site were found. No alternative splicing was observed in right ventricle or brain cortex. The gene structure of canine KCNJ2 and KCNJ12 was conserved amongst other vertebrates, while current Genbank gene annotation was determined as incomplete. In silico translation of KCN12 revealed a non-conserved glycine rich stretch located near the carboxy-terminus of the KIR2.2 protein. However, no differences were observed when comparing dog with human KIR2.2 protein upon ectopic expression in COS-7 or HEK293 cells with respect to subcellular localization or electrophysiological properties.